Hepatic fibrosis as an additional risk factor for the development of cardiovascular disorders in patients with type 2 diabetes mellitus with non-alcoholic fatty liver disease - O.M. Bilovol; I.I. Kniazkova; O.V. Zemlianitsyna; I.P. Dunaieva; I.P. Romanova; O.D. Kurilo; V.M. Sinaiko; N.O. Kravchun (Medičnì Perspektivi)
The aim of the study was to determine the relationship between the degree of progression of liver fibrosis and the risk of cardiovascular complications in patients with Type 2 diabetes mellitus (DM) with non-alcoholic fatty liver disease (NAFLD). The study included 110 patients with Type 2 diabetes (62 men and 48 women), the average age of the subjects was 52.07±1.11 years. All patients were divided into 2 groups: the main group included 72 patients with Type 2 diabetes with concomitant NAFLD (38 men and 34 women); the control group included 38 patients with Type 2 diabetes without clinical manifestations of NAFLD (24 men and 14 women). Patients of the main group were divided into 3 subgroups, taking into account the predominant pathological processes in the clinical picture. The division into subgroups was carried out in 2 stages: at the first stage, those with predominant manifestations of liver fibrosis (F2 or more) were selected from the general population of patients with Type 2 diabetes with NAFLD according to the results of liver elastography and the use of Bonacini and Metavir scales. The number of such patients was 29, which accounted for 40.3% of the total number of patients in the main group. The remaining patients were divided into 2 subgroups: 11 patients (15.3%) had non-alcoholic liver steatosis, and 32 patients (44.4%) had signs of non-alcoholic steatohepatitis (NASH). As a result of the study, it was found that the presence of liver fibrosis in patients with Type 2 diabetes with NAFLD is significantly more often associated with cardiovascular complications, such as arterial hypertension, coronary heart disease, myocardial infarction, stroke, diabetic retinopathy and nephropathy. A significant decrease in the ejection fraction (EF) was found in patients with Type 2 diabetes with concomitant NAFLD. At the same time, the number of patients with EF disorders of varying degrees in the main group significantly exceeded that in the comparison group (33.3% and 6.7%, respectively, p<0.001). The average values of left ventricular myocardial mass are significantly lower in patients with NASH and fibrosis formation compared to patients with NAFLD at the stage of fatty hepatosis. There was also a significant decrease in the size of the left and right atria in patients with NASH compared to both patients with steatosis and patients with fibrotic liver changes. Patients with predominant fibrotic changes in the liver are characterized by a relative decrease in myocardial mass, a decrease in final diastolic and systolic volumes and EF, which may indicate the development of diastolic dysfunction in them. It is shown that it is necessary to take into account in clinical practice not only the generally accepted stages of NAFLD, but also the predominant pathological process in the liver in patients with Type 2 diabetes, namely steatosis, manifestations of inflammation and fibrotic disorders. It is proved that fibrotic changes in the liver can develop at all stages of liver tissue damage.